A simple and safe brick masonry infill construction for high seismic-prone area. Issue 1 (September 2020) - Tanjung, J; Ismail, FA; Maidiawati, M; Hayati, Y
Abstract: West Sumatera Province has been known as one of the high seismic-prone areas in Indonesia. In this area, peoples commonly use the brick masonry as infill in the Reinforced Concrete (RC) frame structures. Field investigation after the earthquake informed that there were many bricks masonry infill collapsed caused by the earthquake motion. In this study, a simple and safe brick masonry infill construction in the RC frame structure is proposed for applying in the high seismic-prone area such as West Sumatera. The proposed construction method was defined based on the experimental works of the three 1/4 reduced-scale singe-bay and single-story RC frame specimens. The specimens include one specimen of RC frame infilled with brick masonry, one specimen of RC frame infilled with strengthened brick masonry by using chicken wire mesh, and one specimen of RC frame infilled with brick masonry infill and anchored to the columns with plain steel rebars. The wire mesh was sewn on both sides of the diagonal area of the brick masonry infill. All the specimens have subjected to lateral static reversed loading. The structural test results have shown that the strengthening using the chicken wire mesh increase the lateral strength of the RC frame about 22.%, while the use of the plain rebars anchor decreases the lateral strength about 1.8% and both methods can delay the failure of the brick masonry infill.